2021
DOI: 10.3390/en14133738
|View full text |Cite
|
Sign up to set email alerts
|

Policy Impact on Regional Biogas Using a Modular Modeling Tool

Abstract: Biogas development is expected to contribute to the National Recovery and Resilience plan to overcome the COVID-19 shock. Estimation of the agricultural biogas potential in economic terms can contribute to refining policies inciting effective sector development. In this paper, we attempt to do so by modeling a biogas chain from dedicated crops and livestock waste. This was achieved by coupling farming models to the biogas industry in a partial equilibrium framework. This allows for a comprehensive investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Numerical simulation may help investigators in optimizing operation parameters and forecasting biogas production under different conditions. Providing such estimates and evidence may add value to the existing knowledge in academia and provide more chances for new and additional perspectives in the biogas arena to accomplish the desired biogas sector goals [141]. Tus, a review of this kind has signifcant policy implications for planning, implementing, and expanding biogas plants.…”
Section: Policy Implications and Future Outlookmentioning
confidence: 99%
“…Numerical simulation may help investigators in optimizing operation parameters and forecasting biogas production under different conditions. Providing such estimates and evidence may add value to the existing knowledge in academia and provide more chances for new and additional perspectives in the biogas arena to accomplish the desired biogas sector goals [141]. Tus, a review of this kind has signifcant policy implications for planning, implementing, and expanding biogas plants.…”
Section: Policy Implications and Future Outlookmentioning
confidence: 99%
“…Rozakis et al [8] exploit detailed resource availability analyses, including evidence provided by previous research works, such as Ref. [7], in search of optimal scale specific configurations for regional biomass utilization.…”
Section: Mobilization Of Materials Sources and Knowledge For Sustaina...mentioning
confidence: 99%
“…The first group of papers [4][5][6] is assessing the potentials and relative significance of bioeconomy in the post-COVID economic recovery. This is followed by a group of four papers [7][8][9][10] that are assessing technical or economic feasibility of knowledge-intensive biobased applications at the industrial, or regional, scale. The Special Issue is rounded off with two contributions [11,12] that draw attention to the (often overlooked) role of biotechnology and the commercialization-oriented innovation in the mainstreaming of the economy.…”
Section: Introductionmentioning
confidence: 99%
“…Add to this scenario described before; it is suggested that Modularisation within the biogas context might allow for a comprehensive investigation and application of alternative measures in technology, size, spatial distribution, and land-use change (ROZAKIS et al, 2021), that can leverage its employment.…”
Section: Modularisation Within the Biogas Context Usementioning
confidence: 99%